BUSINESS MODELS OF URBAN SPORTS LIFESTYLE FOR FLEX SPORT HOUSE AND CHANGES OF BUSINESS LEVELS - ALFIANIE 29114892, RISHADEA
Healthy lifestyle is a simple choice that is very appropriate to run. Live with a healthy diet, mind, habit and environment. The urban community recognizes the importance of a healthy lifestyle to avoid these diseases by increasing regular and measurable physical activity, balanced nutritional intake, not smoking, avoiding alcohol consumption, living a clean and healthy lifestyle and managing stress, in Indonesia known as Clean healthy living behavior. To meet the demand of this trend, lately many emerging sports venue businesses located in downtown, close to offices or campus. The establishment of Flex Sport House has a purpose to meet alternative gym which price and place friendly for urban community. The author will analyze business strategies to find target market for Flex Sport House by finding target market industry within greater Bandung West Java. The Research focused on lifestyle Industry. Business issue that would be deeply discussed in this research is how to develop and design a reliable marketing strategy for a new business concept namely Flex Sport House. Analysis of external factors related to the company's industry will be done by using a framework approach PESTEL, Porter's Five Forces and Competitor Analysis. Analysis of internal factors will be done by value chain analysis. From Strategic analysis, the research concluded that Conglomerate diversification, make a decision about the place of business, Made some cooperation with external parties, Create new trainer and upgrade the trainer skill, and Massive promotion thru Social media, get much follower to be implemented at Flex Sport House.